Danish Women Want to Participate in a Hypothetical Breast Cancer Screening with Harms and No Reduction in Mortality: A Cross-Sectional Survey. (May 2023) - Røssell, Eeva-Liisa; Bo, Anne; Grønborg, Therese Koops; Kristiansen, Ivar Sønbø; Borgquist, Signe; Scherer, Laura D.; Støvring, Henrik
Introduction: Informed decision making is recommended in breast cancer screening. Decision aids with balanced information on harms and benefits are recommended to support informed decision making. However, informed screening decision making may be challenged by overly positive attitudes toward cancer screening. We hypothesized that a substantial proportion of Danish women would want to participate in screening regardless of the presented information. Therefore, we aimed to estimate the prevalence of Danish women wanting to participate in a hypothetical breast cancer screening offering no reduction in breast cancer mortality but potential harms related to unnecessary treatment. Methods: In a cross-sectional study, we invited a random sample of 751 women in the nonscreening population aged 44 to 49 y in the Central Denmark Region to an online questionnaire using the official digital mailbox system. The questionnaire included a description of a hypothetical screening and questions about thoughts on breast cancer, health literacy, and questions on the assessment of the hypothetical screening including intended participation, understanding, and belief in information. Data were linked to register data on sociodemographic factors. Results: In total, 43.0% (323/751) responded to the questionnaire. Of these, 247 (82.3% [95% confidence interval: 77.5–86.5]) wanted to participate in the hypothetical breast cancer screening (participation group). More than two-thirds in both the participation group and nonparticipation group seemed to understand the presented information. Half of the women who understood the information disbelieved it. Conclusions: Exceeding our expectations, a majority of women wanted to participate in a hypothetical screening with potential harms but no reduction in breast cancer mortality. A large proportion understood but disbelieved the screening information. This could indicate that Danish women make their screening decisions based on beliefs rather than presented screening information. This study was registered at ClinicalTrials.gov (Identifier: NCT04509063) Highlights: The majority of Danish women wanted to participate in a hypothetical breast cancer screening with potential harms related to unnecessary treatment but no reduction in mortality. A large proportion of women understood but disbelieved the hypothetical screening information. Informed decision making may be challenging when women disbelieve the information they receive. Enthusiasm for cancer screening and potential disbelief in information are important factors when developing and improving screening information and invitation.